Self-Management of Oxaliplatin-Related Peripheral Neuropathy in Colorectal Cancer Survivors. (25th August 2013) - Tofthagen, Cindy; Gonzalez, Laura; Visovsky, Constance; Akers, Alex
Abstract : Purpose . The purpose of this study was to evaluate medications that cancer survivors with oxaliplatin-induced peripheral neuropathy take to control neuropathic symptom, and to explore self-management techniques used at home to provide temporary relief of painful neuropathy. This was a mixed methods, descriptive, cross-sectional study using self-reported data from colorectal cancer survivors previously treated with oxaliplatin. We analyzed demographic and medication data obtained from participants, along with written comments from an open-ended question regarding methods participants had tried to self-manage symptoms of neuropathy. Results . Twenty-nine percent of the sample reported taking some type of nutritional supplement with potential neuroprotective qualities. Opioids were being taken by 10% of the sample, and nonsteroidal anti-inflammatory and over-the-counter medications were taken by 15% of participants. Twelve percent of participants were taking antidepressants and 10% were taking anticonvulsants, primarily gabapentin. Recurrent themes for nonpharmacologic treatment included avoiding the cold/keeping warm, keeping moving, massaging or rubbing the affected area, and living with it. Conclusions . Patients treated with oxaliplatin for colorectal cancer utilize a variety of traditional pharmacologic agents and nutritional supplements in an effort to self-manage neuropathic symptoms. Patients also employ a variety of home-based therapies to provide temporary relief of peripheral neuropathy symptoms.